Late Deep Infections Complicating Percutaneous Pinning of Supracondylar Humerus Fractures - Achraf H. Jardaly; Ketrick LaCoste; Shawn R. Gilbert; Michael J. Conklin (Case Reports in Orthopedics)
Objectives. Complications following treatment of supracondylar humerus fractures are typically seen shortly postoperatively. Late complications occurring years after percutaneous pinning are rare but can be indolent and have permanent sequelae. We present cases of children presenting with late deep infections to discuss their diagnosis and treatment. Methods. After institutional review board approval, we retrospectively reviewed records of three children who developed deep infections at least one year after percutaneous pinning of their supracondylar humerus fracture. Patient details and outcomes were analyzed. Radiographs and magnetic resonance imaging were reviewed along with each patient’s clinical course and treatment. Results. We report 3 cases of osteomyelitis and/or septic arthritis presenting at least one year after supracondylar humerus fractures treated with closed reduction and percutaneous pinning. The patients required several irrigation and debridement procedures with placement of antibiotic beads in addition to a prolonged course of antibiotics. Conclusion. Delayed deep infections can occur after closed reduction and percutaneous pinning of supracondylar humerus fractures in children. Vigilance is required to diagnose and treat such occurrences, and prolonged follow-up is needed to monitor for recurrent or intractable infections.